Samarcandin protects against testicular ischemia/reperfusion injury in rats via activation of Nrf2/HO-1-mediated antioxidant responses - Maged S. Abdel-Kader; Rehab F. Abdel-Rahman; Hassan N. Althurwi; Gamal A. Soliman; Hanan A. Ogaly; Faisal F. Albaqami (Elsevier, 2023)
The purpose of this study was to evaluate the effectiveness of samarcandin (SMR) in preventing testicular injury caused by ischemia/reperfusion (I/R) in rats. Rats were divided into 4 groups at random: the sham group, the T/D control group (CONT), the T/D group receiving SMR treatment at 10 mg/kg (SMR-10), and the T/D group receiving SMR treatment at 20 mg/kg (SMR-20). When compared to the CONT group, SMR improved the oxidant/antioxidant balance by reducing malondialdehyde (MDA), nitric oxide (NOx), and increasing reduced glutathione (GSH), gluta-thione peroxide (GSH-Px), and superoxide dismutase (SOD). Moreover, SMR increased the levels of the steroid hormones' testosterone (TST), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) in the blood as well as controlled the inflammatory mediators; interleukin-6 (IL6), tumor necrosis factor alpha (TNF-α), and nuclear factor κB (NF-κB). Nevertheless, SMR-treated animals showed a considerable downregulation of the apoptotic marker caspase-3. The T/D-induced histopathological changes were reduced and Proliferating Cell Nuclear Antigen (PCNA) protein expression was enhanced by SMR. These effects are associated with upregulation of testicular (Nuclear factor erythroid 2-related factor 2 (Nrf2), Heme oxygenase-1 (HO-1), and downregulation of NF-κB mRNA expression levels. These findings suggest that SMR may be able to prevent T/D-induced testis damage by mainly regulating the expression of Nrf2 and NF-B, which seems to mediate its promising antioxidant, anti-inflammatory and antiapoptotic effects seen in this study.